MEMBANDINGKAN KECEPATAN SINYAL WIFI ID DENGAN SINYAL WIFI WARUNG KOPI MENGGUNAKAN NET SPEED MONITOR - Habibi, Anang; Hakim, Izzuddin Naufal; Nizarudin, Muhammad; Putra, Bima Variandana (Pusat Riset dan Inovasi Nasional, 2023)
In this modern era, of course we are no strangers to advanced technology called the internet. To be able to connect data globally, an intermediary is needed which is commonly called an internet signal. Because a job is affected by how fast the internet signal is, this study aims to compare the signal strength at the maximum distance of the internet signal between wifi id and wifi coffee shop. Determination of QoS parameters is done by measuring internet access speed with Net Speed Monitor and measuring Upload and Download. Factors affecting the difference in signal speed are the type of device, the transmission medium and the resistance.